Water Quality Analysis of Agriculturally Impacted Tidal Blackbird Creek, Delaware - Stone, Matthew L.; Roeske, Kristopher; Chintapenta, Lathadevi K.; Phalen, Laurieann; Kalavacharla, Venugopal; Ozbay, Gulnihal (Frontiers in Environmental Science, 2016)
Blackbird Creek, Delaware is a small watershed in northern Delaware that has a significant proportion of land designated for agricultural land use. The Blackbird Creek water monitoring program was initiated in 2012 to assess the condition of the watershed’s habitats using multiple measures of water quality. Habitats were identified based on percent adjacent agricultural land use. Study sites varying from five to fourteen were sampled biweekly during April and November, 2012-2015. Data were analyzed using principal component analysis and generalized linear modeling. Results from these first four years of data documented no significant differences in water quality parameters (dissolved oxygen, pH, temperature, salinity, inorganic nitrate, nitrite, ammonia, orthophosphate, alkalinity, and turbidity) between the two habitats, although both orthophosphate and turbidity were elevated beyond EPA-recommended values. There were statistically significant differences for all of the parameters between agriculture seasons. The lack of notable differences between habitats suggests that, while the watershed is generally impacted by agricultural land use practices, there appears to be no impact on the surface water chemistry. Because there were no differences between habitats, it was concluded that seasonal differences were likely due to basic seasonal variation and were not a function of agricultural land use practices.